REVITALISASI TEMPAT HIBURAN BERBASIS BUDAYA DI KOTA SURABAYA - Marcerino Restu Putra Lianto (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
Revitalization of entertainment and cultural tourism venues in Surabaya City is a strategic step to restore the cultural spirit that is the identity of this city. This study uses a qualitative approach with a phenomenological method to understand the community's experience of various tourist locations, including Kota Tua, Kya-Kya, Alun-Alun Surabaya, Jalan Tunjungan, and Gedung Cak Durasim. The discussion in the article links relevant theories in the role of government and society in utilizing culture in the form of tourism, and community interactions based on cultural symbols. Through in-depth observations and interviews, this study reveals the social dynamics and interactions between local communities and tourists. The results of the analysis show that revitalization is not only aimed at attracting visitors but also strengthening a sense of ownership of cultural heritage. For example, the arrangement of Kota Tua is expected to revive the atmosphere of the past. With these revitalization steps, it is hoped that these places will not only become tourist attractions but also a means of preserving culture and historical education for future generations. This study makes a significant contribution to understanding the importance of revitalizing cultural tourism venues in efforts to preserve cultural heritage in Surabaya City.